2016
DOI: 10.1055/s-0042-103687
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites from the Culture of the Marine Sponge-Associated Fungi Talaromyces tratensis and Sporidesmium circinophorum

Abstract: Wortmin (1), meso-1,4-bis(4-methoxybenzyl)-2,3-butanediol (2), and a new isocoumarin derivative tratenopyrone (3) were isolated from the marine sponge-associated fungus Talaromyces tratensis KUFA 0091. A new diphenyl ether derivative, circinophoric acid (4), was isolated, together with the previously reported anthraquinones catenarin and physcion, the benzophenone monomethylsoluchrin, and β-ergosterol-5,8-endoperoxide, from the marine sponge-associated fungus Sporidesmium circinophorum KUFA 0043. The structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Other known compounds were identified as 18-oxotryprostatin A ( 3 ) [ 22 ], sulochrin ( 5 ) [ 26 ], monomethylsulochrin ( 6 ) [ 23 ], 6-methoxyspirotryprostatin B ( 7 ) [ 22 ], spirotryprostatin A ( 8 ) [ 27 ], spirotryprostatin C ( 9 ) [ 28 ], pseurotin A ( 11 ) [ 25 ], azaspirofuran A ( 12 ) [ 29 ], demethoxyfumitremorgin C ( 13 ) [ 30 ], fumitremorgin C ( 14 ) [ 28 ], 13-oxofumitremorgin B ( 15 ) [ 31 ], fumitremorgin B ( 16 ) [ 28 ], verruculogen ( 17 ) [ 28 ], helvolinic acid ( 18 ) [ 32 ], helvolic acid ( 19 ) [ 33 ], fumiquinazolines J ( 20 ) [ 34 ], chaetominine ( 21 ) [ 35 ], fumigaclavine C ( 22 ) [ 36 ], 9-deacetylfumigaclavine C ( 23 ) [ 36 ], fumagiringillin ( 24 ) [ 37 ], asterric acid ( 25 ), circinophoric acid ( 26 ) [ 38 ], dimethyl 2,3′-dimethylosoate ( 27 ) [ 23 ], methylated asterric acid ( 28 ) [ 39 ], endocrocin ( 29 ) [ 40 ], and questin ( 30 ) [ 41 ]. Their 1 H and 13 C NMR data were identical to those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Other known compounds were identified as 18-oxotryprostatin A ( 3 ) [ 22 ], sulochrin ( 5 ) [ 26 ], monomethylsulochrin ( 6 ) [ 23 ], 6-methoxyspirotryprostatin B ( 7 ) [ 22 ], spirotryprostatin A ( 8 ) [ 27 ], spirotryprostatin C ( 9 ) [ 28 ], pseurotin A ( 11 ) [ 25 ], azaspirofuran A ( 12 ) [ 29 ], demethoxyfumitremorgin C ( 13 ) [ 30 ], fumitremorgin C ( 14 ) [ 28 ], 13-oxofumitremorgin B ( 15 ) [ 31 ], fumitremorgin B ( 16 ) [ 28 ], verruculogen ( 17 ) [ 28 ], helvolinic acid ( 18 ) [ 32 ], helvolic acid ( 19 ) [ 33 ], fumiquinazolines J ( 20 ) [ 34 ], chaetominine ( 21 ) [ 35 ], fumigaclavine C ( 22 ) [ 36 ], 9-deacetylfumigaclavine C ( 23 ) [ 36 ], fumagiringillin ( 24 ) [ 37 ], asterric acid ( 25 ), circinophoric acid ( 26 ) [ 38 ], dimethyl 2,3′-dimethylosoate ( 27 ) [ 23 ], methylated asterric acid ( 28 ) [ 39 ], endocrocin ( 29 ) [ 40 ], and questin ( 30 ) [ 41 ]. Their 1 H and 13 C NMR data were identical to those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…)-associated fungi, Talaromyces tratensis and Sporidesmium circinophorum (Gulf of Thailand), wortmin (1), meso-1,4-bis(4-methoxybenzyl)-2,3-butanediol (2), and isocoumarin derivative tratenopyrone (3) were synthesized by the former, while the latter produced diphenyl ether derivative, circinophoric acid (4), and other known compounds, catenarin, physcion, mono-methylsoluchrin, and β-ergosterol-5,8-endoperoxide. None of the compounds inhibited C. albicans ATCC 10232 (> 512 µg/mL) [102].…”
Section: Invertebrate-associated Fungi (Sponges Ascidians Crab)mentioning
confidence: 95%
“…Evidence has emerged, demonstrating that many natural products extracted from marine animals and algae are the products of associated microorganisms, mostly bacteria, and fungi (Raghukumar 2008). Spongeassociated fungi have the potential to produce new chemical entities (Volgraf et al 2008;Blunt et al 2010;Vasanthabharathi 2012;Vicente et al 2013;Bolanos et al 2015;Imhoff 2016;Indraningrat et al 2016) that actively inhibited the growths of various pathogenic microorganisms (Khoeri et al 2011;Mayer et al 2013;Radjasa et al 2013;Buttachon et al 2016;Corral et al 2018). Our previous research also showed that spongeassociated fungi have several bioactivities such as anti-S. aureus and E. coli (Wittriansyah et al 2016), antibacterial produced by sponge Agelas sp.…”
Section: Introductionmentioning
confidence: 97%